2010
DOI: 10.1074/jbc.m109.093286
|View full text |Cite
|
Sign up to set email alerts
|

Topological Location and Structural Importance of the NBCe1-A Residues Mutated in Proximal Renal Tubular Acidosis

Abstract: NBCe1-A electrogenically cotransports Na

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
90
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(93 citation statements)
references
References 24 publications
2
90
0
1
Order By: Relevance
“…Forty-eight hours after transfection, HEK 293 cell membranes were prepared as described (46). [ 14 C]NEM labeling was performed as described previously (13) -free solution and monitoring the pHi changes.…”
Section: Protein Expression and [ 14 C]nem Labelingmentioning
confidence: 99%
See 3 more Smart Citations
“…Forty-eight hours after transfection, HEK 293 cell membranes were prepared as described (46). [ 14 C]NEM labeling was performed as described previously (13) -free solution and monitoring the pHi changes.…”
Section: Protein Expression and [ 14 C]nem Labelingmentioning
confidence: 99%
“…The COOH-terminal cytoplasmic tail is critically involved in NBCe1-A plasma membrane processing (22,26,38). The transmembrane region of NBCe1-A contains 14 transmembrane segments (TM), and the last five TMs may participate in forming a scaffold to accommodate NBCe1-A substrate ion interaction sites (45,46). Three amino acids in NBCe1-A-TM1 (Ala428, Ala435, and Thr442) (44) and one amino acid in TM8 (Leu750) (25) have been determined to line the ion permeation pathway and are potentially involved in ion translocation.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Topological analysis using the substituted cysteine accessibility method suggests that most of these mutations are buried in the protein complex/lipid bilayer where they perform important structural roles [38]. In particular, the amino acid substitution analysis revealed that Thr 485 might reside in a special position, which seems to require the OH group side chain to maintain a normal conformation of NBCe1A.…”
Section: Nbce1 Mutations and Prtamentioning
confidence: 99%